Home births in the context of free health care: The case of Kaya health district in Burkina Faso. Issue 1 (November 2016) - Kouanda, Seni; Bado, Aristide; Meda, Ivlabèhiré Bertrand; Yameogo, Gisèle S.; Coulibaly, Abou; Haddad, Slim
Abstract: Objective: To identify the factors associated with home births in the Kaya health district in Burkina Faso, where child delivery was free of charge between 2007 and 2011. Methods: Both qualitative and quantitative data were collected from the Kaya Health and Demographic Surveillance System (Kaya HDSS) among women who delivered at home or in a health facility between January 2008 and December 2010. Multilevel logistic regression was applied to quantitative data, while the qualitative data were analyzed thematically based on emerging themes, subthemes, and patterns across group and individual cases. Results: The findings indicate that 12% (n = 311) of childbirths occurred at home (n = 2560). Key factors associated with home birth were age, distance from the household to the primary health center, and prenatal visits. The qualitative analysis showed that immediate child delivery, previous experience of giving birth at home, negative experiences with health centers, fear of cesarean delivery, and lack of transport are key predictors of home births. Conclusion: Though relevant, addressing the financial barrier to health care is not enough. Additional measures are necessary to further reduce the rate of home births.